Mild Form of Treacher Collins Syndrome Imitating Juvenile Otosclerosis. (16th August 2012) - Zeleník, Karol; Komínek, Pavel
Abstract : Treacher Collins syndrome (TCS) is an inherited developmental disorder. More than 40% of individuals with TCS have conductive hearing loss attributed to external and middle ear anomalies. Mild cases of TCS often pass undiagnosed at birth or early childhood. The disease may be manifested as conductive hearing loss in teenagers and may resemble juvenile otosclerosis. Patients could suffer from slight facial variabilities including retrognathia (as in our case) and others, which point out to a possible middle ear anomaly. Surgical corrections of middle ear anomalies including TCS generally lead to poorer outcomes comparing with juvenile otosclerosis, which should be discussed with parents during preoperative counselling.